Trimethylamine Induced Chronic Kidney Injury by Activating the ZBP1-NLRP3 Inflammasome Pathway - Bai, L; Chen, Q; Li, Y; Wu, F; Jin, M; Chen, Y; Teng, X; Jin, S; Fan, H; Wu, Y (Physiological research, 2024)
Trimethylamine N-oxide (TMAO), a bioactive metabolite of gut microbes, plays a pivotal role in the pathogenesis of kidney diseases by activating programmed cell death (PCD) pathways. However, whether trimethylamine (TMA) contributes to chronic kidney injury and which kind of PCD is involved in TMA-induced chronic kidney injury has not been previously evaluated. To observe the effect of TMA, male C57BL/6J mice were randomly divided into two groups: the Control group and the TMA group. The mice in the TMA group were intraperitoneally injected with 100 micromol/kg/day TMA for three months, whereas the mice in the Control group were injected with normal saline for the same period. After three months, plasma creatinine and blood urea nitrogen levels, indicators of kidney function, increased significantly in the TMA group as compared with those in the Control group. Furthermore, Masson staining assay showed that TMA treatment led to a larger area of fibrosis than the Control group. TMA treatment did not change the Bax/Bcl-2 ratio, RIP1, RIP3 and MLKL phosphorylation, or iron and malondialdehyde levels in kidney tissues, indicating that apoptosis, ferroptosis and necroptosis were not involved in TMA-induced chronic kidney injury. However, compared with the Control group, TMA treatment significantly upregulated NLRP3, Caspase-1, IL-1beta, cleaved-Caspase 8, Caspase-8, and ZBP1 protein expression in kidney tissues. These results indicated that the ZBP1-NLRP3 inflammasome pathway was involved in TMA-induced chronic kidney injury. In conclusion, our studies revealed that the ZBP1-NLRP3 inflammasome may take part in the progression of TMA induced chronic kidney injury.
Keywords: signální transdukce; Inflammasomes; protein NLRP3; Renal Insufficiency, Chronic; chronická renální insuficience; Methylamines; myši inbrední C57BL; mužské pohlaví; Signal Transduction; Mice; methylaminy; zvířata; NLR Family, Pyrin Domain-Containing 3 Protein; ledviny; inflamasomy; myši; Kidney; Mice, Inbred C57BL; Male; Animals